Male homosexuality in the pronouns of the sanatorio pinel 1920-1940: Study of understanding the devices of social control - Nascimento, Francisco Arrais [UNESP]; de Mello Lima, Larissa [UNESP]; Martínez-Ávila, Daniel [UNESP] (Universidade Federal da Paraíba, 2020)
The objective of this study was to understand how the discursive universe about homosexuality was constituted through the unraveling of the components of the social control device, under the bias of the pathologization, as a component of the triad sin-crime-disease. (records) produced by health professionals related to Pinel sanatorium in the period between 1920-1940. It is emphasized that the behavior and perceptions of the body of such patients were identified and classified with the purpose of controlling and justifying the withdrawal of such subjects from social life, under a discursively pathological aegis. Methodologically it was proposed the construction of a cartography of documents in order to identify according to Rolnik (1989) psychosocial, political and affective landscapes. In view of this, it was proposed to enter the sphere of the gender discussions, situating itself theoretically-methodologically in a discursive-deconstructionist perspective, resorting to Foucaultian-based post-structuralist studies and also to the analysis of the French orientation discourse, as well as the relation with the theorizations queer Therefore, it can be understood that the device that transforms and resigns in a way to survive and better serve the desires of the hegemonic groups, spreading in such a way as to make it impossible for the being not to be considered as subject in its nature, creating a system excluding and (Church, State, among others) echo and certify the performance and maintenance of the historical devices of social control, causing them to be introjected by society, thus generating docile and productive subjects.
Homossexualidade masculina nos prontuários do sanatorio pinel 1920-1940: Um estudo de compreensão dos dispositivos de controle social
Keywords: Devices of Social Control; Male Homosexuality; Patient Record; Representation; Sanitorium Pinel